BATHTUB - KIKUHARA KEIMEI; SATO YOSUKE; YAMAZAKI HARUO; KITAMURA SOETSU; KAMIYA TOKIMASA; SHIRAI YASUHIRO (2009)
PROBLEM TO BE SOLVED: To provide a bathtub which can properly discharge polluted matters such as dirt and dust in bathtub water outside. SOLUTION: The bathtub is so constructed that several water stream generating openings 2 which spout water and generate water streams in the bathtub water are arranged in the bottom of the bathtub. Also, the bathtub is so constructed that an outlet 3 of the bathtub water is arranged in the position of the bathtub water level in the side of the bathtub so that dirt and dust can be led to the outlet 3 by the water streams which are spouted from the water stream generating openings 2. COPYRIGHT: (C)2009,JPO&INPIT